Sex change in Piper thomsoni Hook . (Piperaceae) - V A Parthasarathy, K V Saji, B Sasikumar, K Johnson George (Journal of Spices and Aromatic Crops, 2005)
Piper thomsoni, a dioecious Piper species endemic to north eastern India, was coll ected from Totopara forests (New Jalpaiguri District, West Bengal), multiplied and maintained at the Germplasm Conservatory, Experimental Farm, Indian Institute of Spices Research, Peruvannamuzhi (Kerala). The male plants conserved under partial shade exhibited sex change and a few berries developed on the spike. This appears to be the first report of sex change in the genus Piper.